1998
DOI: 10.1055/s-2007-978918
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Roles of Angiotensin II Type 1 and Type 2 Receptors in Human Adrenals

Abstract: Although stimulation of aldosterone secretion is one of the functions of angiotensin II, the gene expression and biological significance of the angiotensin II receptor subtypes, AT1 and AT2, in the human adrenal have not been characterized. We therefore investigated the transcription levels of the receptor subtype genes and their roles in regulation of steroid secretion by human adrenals. The expression of AT1 and AT2 receptor mRNA was assessed by reverse transcription-polymerase chain reaction followed by Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…23 In adrenal tissues, both the AT2 receptor and the AT1 receptor are thought to stimulate aldosterone secretion. 5 Although AT1 is the predominant receptor subtype, accounting for 80% of the Ang II receptors in rat and bovine adrenal glands, 24 a contribution of the AT2 receptor could be potentiated if the AT1 receptor is chronically blocked. Therefore, the second potential mechanism of aldosterone breakthrough in our study was that the increased Ang II stimulates aldosterone secretion through the AT2 receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 In adrenal tissues, both the AT2 receptor and the AT1 receptor are thought to stimulate aldosterone secretion. 5 Although AT1 is the predominant receptor subtype, accounting for 80% of the Ang II receptors in rat and bovine adrenal glands, 24 a contribution of the AT2 receptor could be potentiated if the AT1 receptor is chronically blocked. Therefore, the second potential mechanism of aldosterone breakthrough in our study was that the increased Ang II stimulates aldosterone secretion through the AT2 receptor.…”
Section: Discussionmentioning
confidence: 99%
“…4 In addition, we have demonstrated that the AT2 receptor may be involved in the stimulation of aldosterone secretion. 5 Selective antagonism of the AT1 receptor is known to be associated with a substantial increase in plasma Ang II levels. 6 It is therefore suggested that the increased plasma Ang II may stimulate aldosterone secretion through the AT2 receptor with the AT1 receptor blocked.…”
mentioning
confidence: 99%
“…This observation is compatible with some data from earlier papers. Tanabe et al [8] and Kitamura et al [12] reported on the expression of AT1 mRNAs in both aldosterone-and cortisol-secreting adenomas. Opocher et al [11] studied the binding of labeled Ang II in presence or absence of specific receptor blockers concluded that Ang II receptors are present in both aldosterone-sereting and cortisol-secreting adenomas, but in the latter the receptor density is lower than in the normal adrenal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Although the adrenal gland is affected by circulating Ang II, the peptide can be also generated within the gland by a local reninangiotensin system [4,5]. Both main subtypes of Ang II receptors, AT1 and AT2 were identified in rodent and human adrenal cortex and medulla [6][7][8]. In adrenal cortex, AT1 subtype is prevalent, whereas in adrenal medulla the AT2 subtype dominates [6].…”
Section: Introductionmentioning
confidence: 99%
“…Dogs, baboons, and probably pigs can be used as animal models for human AT 1 R imaging since, in contrast to rodents in which two subtypes, AT 1a and AT 1b , have been discovered, dogs, baboons and pigs, like humans, possess only one subtype of these receptors, i.e., AT 1 R. The PET images showed high [ 11 C]KR31173 binding in the adrenal glands of dogs and a baboon, confirming the ex vivo binding studies performed in mice. The adrenals have a very high density of the AT 1 R which also undergoes hormonal regulation [7,29] and is involved in the regulation of the biosynthesis and secretion of aldosterone [30][31][32][33]. Of potential interest for imaging studies is the application of AT 1 R PET in aldosterone producing tumors.…”
Section: Discussionmentioning
confidence: 99%